Estradiol and progesterone levels in early pregnancy after natural, estradiol + progesterone or gonadotrophin stimulated frozen embryo transfer cycle: a randomised controlled trial protocol - Nina Freiesleben Mørch; Mette Petri Lauritsen; Pernille Fog Svendsen (BMJ Open)
Introduction Frozen embryo transfer is being increasingly used for assisted reproductive therapy and offers similar pregnancy rates as treatment with fresh embryo transfer. In women with regular menstrual cycles, transfer of a frozen thawed blastocyst can be performed in either natural cycle or substituted cycle. Anovulatory women can only be offered a substituted or a stimulated cycle. Knowledge on fetal exposure to estradiol in early pregnancy is very limited, but studies on mice and rats have shown hormonal and metabolic disturbances in cubs born from estradiol-exposed mothers. We aim to investigate serum estradiol and progesterone levels in women who conceived after natural, estradiol and progesterone, or gonadotrophin stimulated frozen embryo transfer.Methods and analysis The study is an open-label, randomised controlled trial with normo-ovulatory women being randomised to natural cycle or estradiol and progesterone substitution and anovulatory women being randomised to estradiol and progesterone substitution or gonadotrophin stimulation. Serum estradiol and progesterone will be measured every 2 weeks from cycle days 2–3 until gestational age 9+6. Serum levels will be compared according to treatment regimens and cycle length. Furthermore, obstetric outcomes (live birth rates, birth weight, gestational age at birth, complications and malformations) and a possible association with serum estradiol and progesterone levels will be evaluated.Ethics and dissemination The three treatment regimens are all standard treatments and are comparable with regard to pregnancy rates. Patients will be following routine treatments and thus discomforts are limited to routine transvaginal ultrasound scans and additional blood testing. The study is approved by the Scientific Ethical Committee of the Capital Region of Denmark and the Danish Medicines Agency. The study will be carried out in accordance with the Declaration of Helsinki and monitored by a good clinical practice unit. Positive, negative and inconclusive findings will be published in international peer-reviewed journals.Trial registration number NCT04997525, 2020-001218-39.